Hidden in Plain Sight — Reconsidering the Use of Race Correction in Clinical Algorithms - Vyas, Darshali A; Eisenstein, Leo G; Jones, David S (The New England journal of medicine, 2020)
Diagnostic algorithms and practice guidelines that adjust or “correct” their outputs on the basis of a patient’s race or ethnicity guide decisions in ways that may direct more attention or resources to white patients than to members of racial and ethnic minorities.